Ornament and European modernism from art practice to art history - Vandi, Loretta (Routledge Research in Art History, 2017)
These in-depth, historical, and critical essays study the meaning of ornament, the role it played in the formation of modernism, and its theoretical importance between the mid-nineteenth century and the late twentieth century in England and Germany.